Annexin A2 Egress during Calcium-Regulated Exocytosis in Neuroendocrine Cells - Marion Gabel (Cells, 2020)
Annexin A2 (AnxA2) is a calcium- and lipid-binding protein involved in neuroendocrine secretion where it participates in the formation and/or stabilization of lipid micro-domains required for structural and spatial organization of the exocytotic machinery. We have recently described that phosphorylation of AnxA2 on Tyr23 is critical for exocytosis. Considering that Tyr23 phosphorylation is known to promote AnxA2 externalization to the outer face of the plasma membrane in different cell types, we examined whether this phenomenon occurred in neurosecretory chromaffin cells. Using immunolabeling and biochemical approaches, we observed that nicotine stimulation triggered the egress of AnxA2 to the external leaflets of the plasma membrane in the vicinity of exocytotic sites. AnxA2 was found co-localized with tissue plasminogen activator, previously described on the surface of chromaffin cells following secretory granule release. We propose that AnxA2 might be a cell surface tissue plasminogen activator receptor for chromaffin cells, thus playing a role in autocrine or paracrine regulation of exocytosis.